A correlation of hysterolaparoscopic findings and BACTEC culture in infertility - Guru, Mahesweta; Deshmukh, Prasad Yeshwant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is agonising condition. Tuberculosis is an important health problem worldwide. One third of the world’s population is currently affected with tuberculosis. Hysterolaparoscopy is a well-recognized procedure for the diagnosis of infertility. Culture for TB bacilli is the gold standard for diagnosis of genital TB. Methods: Infertile women undergoing dilatation and curettage with hysterolaparoscopy with normal husband semen analysis as a part of their infertility workup at M. G. M. Medical Hospital, Kalamboli. Sample size: 30. Results: Incidence of GTB=22.85%, 25-29 year followed by 35-40 years’ age group was the most common age group was observed. In our study, 74.3% infertility pattern was primary, 25.7% were secondary only 2.85 % (n =1) of the cases of GTB were diagnosed by using TB BACTEC. Laparoscopic findings su0ggested that 18 cases had normal findings and 8 cases had laparoscopic features suggestive of GTB. On chromo pertubation, delayed and absent spillage of the dye was seen in 2 cases. On Hysteroscopy, 29 cases (82.9%) of the patients had normal findings and 3 cases had Hysteroscopic features suggestive of GTB. Conclusions: Genital tuberculosis remains an important under diagnosed cause of infertility. Though culture is considered as gold standard for diagnosis of genital tuberculosis, since GTB is paucibacillary there is an urgent need for more research to come to conclusion whether culture is still gold standard. Further research is required to detect the most sensitive method for diagnosis.